Pengelolaan Kehutanan di Tinjau Berdasarkan Undang-Undang No 41 Tahun 1999 Menyoroti Aspek-Aspek di dalam Hukum Administrasi Negara - Vanessa Uli Sembiring; Salwa Sabrina; Wan Mahrani Sembiring; Muhammad Hafis Faisal; Taufiq Rahmadhan (Demokrasi: Jurnal Riset Ilmu Hukum, Sosial dan Politik, 2024)
State Administrative Law is a legal regulation regarding administration in a country, where the relationship between citizens and their government can run well and safely. In forest management, the need for permits is based on absolute legal provisions which have aspects that must be fulfilled beforehand and regarding the boundaries of each activity in managing forests, the government agrees to supervise them based on Law no. 41 of 1999 concerning Forestry Article 31 paragraph (1) To ensure the principles of justice, equity and sustainability, forest utilization business permits are limited by considering forest sustainability aspects and business certainty aspects. The aim of the research is to determine aspects of forest management. The research method used in this research is literature study by collecting data through articles, the web, books and other sources. The results of the discussion of this research are that forest utilization business permits are limited by considering forest sustainability aspects and business certainty aspects, where these aspects are determinants in managing forests which have been considered previously. The meaning of forest sustainability aspects and business certainty is contained in Article 31 Paragraph (1). What is meant by forest sustainability aspects includes: a. environmental sustainability, b. production sustainability, and c. implementation of social and cultural functions that are fair, even and transparent. What is meant by aspects of business certainty include: a. area certainty, b. certainty of business time, and c. certainty of business legal guarantees.